Career Pathway Barriers, Strategies, and Practices of Female Superintendents in Rural Georgia: A Narrative Inquiry - Rehberg, Erin S. (My University, 2022)
I investigated six rural Georgia female school superintendents’ perceptions of trajectories into the superintendency and their roles and responsibilities as educational leaders. I examined how their life and career experiences shaped their professional roles as practicing female superintendents. This study contributes to the limited academic literature on female superintendents, focusing on the gender obstacles they overcame to find success in a male-dominated career. It also uses the voices of women in rural districts to tell their own stories. I used three conceptual lenses: feminist theory, the gatekeeping theory, and the structural empowerment theory to understand the women's main characteristics of rising to senior leadership positions in a rural school district. I developed four analytical themes from the data: 1) surviving in the male-dominated jungle of educational leadership, 2) being safer at home, 3) the paradox of female leadership, and 4) balancing work-life demands. The findings suggest that female educational leaders adapt and change their behaviors to survive a male-dominated landscape. Although female superintendents are severely underrepresented, they bring to leadership a complete range of the qualities modern leaders need, including self- awareness, resilience, creativity, humility, and authenticity. Male leaders might benefit from these unique characteristics. The research shows the strategies to address the social, political, and economic challenges females face in their day-to-day practices as superintendents. This study's findings are significant for those who mentor female educational leaders, design educational leadership programs and hire school superintendents. Keywords: female superintendents; rural Georgia; feminist theory; educational leadership; superintendents; gatekeeping theory;
Chapter I: INTRODUCTION 1 -- Statement of the Problem 3 -- Purpose 5 -- Research Questions 6 -- Significance 7 -- Conceptual Framework 7 -- Researcher's Interest 8 -- Existing Theory 9 -- Summary of Methodology 12 -- Limitations 13 -- Definition of Terms 14 -- Chapter Summary 15 -- Chapter II: LITERATURE REVIEW 17 -- Conceptual Framework 18 -- Experiential Knowledge 18 -- Existing Theory and Knowledge 20 -- Theories 20 -- Historical Context 23 -- Career Pathways 26 -- Barriers for Female Superintendents 29 -- Characteristics of Female Leaders 37 -- Theories as Connected to the Concepts and Literature 43 -- Summary 44 -- Chapter III: METHODOLOGY 46 -- Research Questions 47 -- Researcher Design and Rationale 47 -- Setting 49 -- Role of Researcher 49 -- Participant Selection 50 -- Data Collection 51 -- Data Analysis 55 -- Issues of Trustworthiness 57 -- Credibility 57 -- Rich Data 58 -- Triangulation 58 -- Member Checking 58 -- Transferability 58 -- Confirmability 59 -- Ethical Procedures 59 -- Chapter Summary 60 -- Chapter IV: NARRATIVES OF FEMALE SCHOOL SUPERINTENDENTS 61 -- Profiles of Participants 63 -- Betty 63 -- Abigail 70 -- Inez 76 -- Rebekah 81 -- Dorothea 86 -- Juliet 93 -- Chapter Summary 99 -- Chapter V: DISCUSSION OF THEMES 100 -- Surviving in the Male-Dominated Leadership Jungle 106 -- Safer at Home 116 -- The Paradox of Female Leadership 123 -- Balancing Work-Life Demands 130 -- Summary 134 -- Chapter VI: CONCLUSION 135 -- Research Questions: Summary Discussion 137 -- Research Question 1… 137 -- Research Question 2 146 -- Implications 152 -- Aspiring Female Superintendents 153 -- Professional Organizations 154 -- School Districts 155 -- School Board Members 156 -- Limitations 156 -- Recommendations for Future Research 158 -- Final Conclusions 160 -- References 166 -- Appendix A: Participant Recruitment Letter 181
Keywords: Dissertations, Academic--United States; Educational leadership; Feminist theory; Georgia; Rural schools; School superintendents; Women school superintendents